O sistema serotonérgico participa da modulação dosmecanismos termorregulatórios e do processo de fadigadurante o exercício prolongado em ratos - Leticia Maria de Souza Cordeiro (2007)
The purpose of the present study was to evaluate the effect of increasedcentral tryptophan (TRP) availability on thermoregulation and metabolic responsesand also on physical performance in rats submitted to exercise until fatigue with orwithout pre-treatment with parachlorophenylalanine (p-CPA), an inhibitor of TRPconversion to serotonin (5-HT). Adult male Wistar rats (250-350g) were used.Intraperitoneal temperature sensors and brain guide cannulae on right lateralcerebral ventricle (RLCV) were implanted under anesthesia. During three daysbefore the experiment, animals were pre-treated with i.p. injections of saline (SAL) orp-CPA. In the day of the experiment, animals were pre-treated with i.p. injections ofeither SAL (0,15M) or TRP (20,3ìM) and underwent a sub maximal exercise untilfatigue (18 m.min-1 and 5% grade; 66%VO2max). The i.c.v. TRP-treated rats whoreceived SAL i.p. showed higher heat storage rate (4,80 ± 0,94cal.min-1 SAL i.c.v. vs.12,60 ± 2,27cal.min-1 TRP i.c.v.; n=7; p=0,01) and also the rate of body temperatureincrease (0,02 ± 0,00°C.min-1 SAL i.c.v. vs. 0,05 ± 0,01°C.min-1 TRP i.c.v.; n=7;p=0,009) than control group, eliciting to a decrease on exercise time to fatigue (70,74± 20,76 min. SAL i.c.v. vs. 22,17± 2,45 min. TRP i.c.v.; n=7; p=0,028). Moreover, wealso found inverse correlations between the rate of body temperature increase andwork produced and between heat storage rate and exercise time to fatigue. Nodifferences were found either on plasma glucose or lactate concentrations at fatiguepoint. The i.p. treatment with p-CPA blocked the effect of TRP on the rate of bodytemperature increase (0,01°C.min-1 SAL i.c.v. vs. 0,01°C.min-1 TRP i.c.v.; n=7) andalso on heat storage rate (2,14 ± 1,10cal.min-1 SAL i.c.v. vs. 1,33 ± 0,57 cal.min-1TRP i.c.v.; n=7). Besides that, the p-CPA administration anticipated heat dissipationboth in the SAL i.c.v. and TRP i.c.v. rats when compared to i.p. SAL treated rats,since 6th minute of exercise their tail skin temperature was already different frombasal. We concluded that the elevated central TRP concentration interfered both onthermoregulation and fatigue mechanisms, without modifying metabolic responses ofexercising rats. These responses were modulated by serotonergic pathways, sinceTRP-induced actions were blocked in the presence of p-CPA, a tryptophanhydroxilase inhibitor. Our data also suggest an effect of the TRP per si on the heatdissipation mechanisms during exercise.